THE USE OF ROSETTA STONE LANGUAGE LEARNING SOFTWARE IN TEACHING LISTENING: DOCUMENTARY RESEARCH - Kurniawan, Dendy; Bunau, Eusabinus; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2021)
This study focused on analyzing the use of Rosetta Stone Language Learning Software in teaching listening comprehension. Based on three previous journal from different universities in Indonesia the writer found that selected institutional repository website in Indonesia discusses about using Rosetta Stone Language Learning Software in teaching listening comprehension. The data described the facts on the use of Rosetta Stone based on the results of research by three researchers which have been published in three scholarly publications in Indonesia. This research is to find out the effectiveness of Rosetta Stone Software in teaching listening comprehension, this study had two data, the primary data (research journals) and secondary data (books). The conclusion that can be taken based on these research reports is the use of Rosetta Stone Software in improving students’ listening skills is effective. There are significant differences in learning listening comprehension between those who had been taught by using Rosetta Stone media and those who had not been taught by using Rosetta Stone media in terms of the scores the students got in the pre-test and post-test.